METHODICAL APPROACH TO THE DETERMINATION OF THE ANTIOXIDANT ACTIVITY OF THE ECHINACEA PURPUREA AND MONARDA FISTULOSA TINCTURES AS A QUALITY CRITERION OF THE DEVELOPMENT OF THEIR COMPOSITION AND LABORATORY TECHNOLOGY - Oksana Yezerska; Nataliia Hudz; Lesya Kobylinska; Anna Filipska; Vira Turkina; Jan Brindza; Piotr Pawel Wieczorek (Acta Medica Leopoliensia)
Aim. The aim of the study was to develop the methodical approach to determine the antioxidant activity of the tinctures of Monarda fistulosa herb and flowers and roots of Echinacea purpurea, as well as to develop their technology in  laboratory conditions.